Modeling conduction in composite spheres with time dependent convective boundary conditions - Application to periodic boiling of eggs - Rajai S. Alassar; Husain Al-Attas (Results in Engineering, 2025)
This study presents a comprehensive analytical solution for heat conduction in a two-layer composite sphere subjected to time-dependent convective boundary conditions. The general model is used to simulate the periodic boiling of eggs, accounting for the distinct thermal properties of the albumen and yolk. It tracks the temperature evolution along the egg’s radius and investigates how cyclic heating influences the internal thermal distribution. It is confirmed that heating profiles can be strategically tailored to achieve specific cooking goals, such as uniform yolk coagulation or maintaining the texture of the albumen. The exact solution has broader applications in food processing industries such as drying of fruits under non-uniform thermal loads.